Developmental changes in muscle size and power characteristics of elite age group swimmers - Barzdukas, A.; Spry, S.; Cappaert, J. M.; Troup, J. P. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
There is a strong relationship between strength development and general growth and maturation during adolescence. The purpose of this study was to determine (1) the characteristic changes in muscle size and power due to growth in elite swimmers and (2) how these changes may affect performance. Measurements of leg and arm power, four skinfold thicknesses and two circumferences were made on 101 female swimmers aged 13.4 to 16.4 and 84 male swimmers aged 14.4 to 17.5 years. Skinfolds and circumference measurements were combined to provide estimates of the muscle/bone component of both the upper and lower extremities. Subjects were divided into three groups based on age and performance level. Group I (male, n = 32, age = 14.4 ± 0.96; female, n = 49, age 13.4 ± 0.95), Group II (male, n = 28, age = 16.4 ± 0.58; female, n = 28, age= 15.4 ± 0.36), and Group III (male, n = 24, age= 17.5 ± 0.61; female, n = 24, age = 16.4 ± 0.39) varied significantly in terms of all anthropometric factors, except height, power variables, and performance times. In summary, (1) the fastest male swimmers were heavier and had higher power values and arm muscle/bone component estimates, and (2) the fastest females had higher power values, arm and leg muscle bone component estimates.